Analisis Pengukuran Kinerja Usaha Mikro Kecil Dan Menengah di Banda Aceh Setelah Mendapatkan Bantuan Pemerintah Selama Masa Pandemi Covid-19 - Safira Nurdin; Sofyan Sofyan; Lukman Hakim (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
The COVID-19 pandemic has had a negative impact on the Micro, Small, and Medium Enterprises sector, the pandemic has been proven to reduce the performance of business actors. To overcome the problems experienced by business actors, the government disbursed several aids, one of which is Micro Business Productive Assistance to micro-business actors affected by the pandemic. The problem in this study is to see how the performance of micro-enterprises in Banda Aceh City before and after receiving assistance. This study aims to analyze the performance of micro-enterprises in Banda Aceh City before and after receiving the Micro Business Productive Assistance program during the COVID-19 pandemic. The research data are primary data obtained from interviews with micro business actors receiving BPUM. Data analysis used the Wilcoxon test to determine the difference between the financial and non-financial performance of micro-enterprises before and after receiving the Productive Assistance for Micro-enterprises, while the Balanced Scorecard approach was used to review the financial performance and non-financial performance of micro-enterprises. The results of this study indicate that there is a significant difference between the financial performance and non-financial performance of micro-enterprises before and after receiving Productive Assistance for Micro Enterprises.